Paradoks Komunikasi-Dakwah Fundamentalis Salafi: Kasus Masjid Nurul Jam’iyah Jambi (The Salafi Fundamentalist Communication-Dakwah Paradox: The Case of The Nurul Jam'iyah Mosque in Jambi) - Adeni Adeni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article aims to analyze the dawa-communication paradoxes of the salafi-fundamentalits by questioning of what is the da’wah form of salafi-fundamentalist, so it is often labeled as intolerant and the term of fundamentalism is accused of being negative? The study focuses on the case of Masjid Nurul Jami’yyah, Jambi. By using qualitative research conducted with interview, observation and documentation, this paper concludes that da’wah of the salafi group is strickly and rigidly done. They are using the top-down communication approach as a seculer model of communication that tend to force da’wah recipients, and ignoiring the Islamic communication model emphasizing egalitarianism and two ways communication giving the recipient the freedom to accept or reject the da’wah message. The paradox of the salafi dawah lies not in the character or substansce of fundamentalism that they stand for, but in the way of da’wa-communication they use. The term of fundamentalism has absolutely no problem in a person’s religious context. Conversely, improper preaching can make the term fundamentalism being negative.